ASSESSMENT OF IRRIGATED SOILS BY THE LEVEL OF DEFLATION SUSCEPTIBILITY - Umarov Muxammad Ismatullayevich; Karimova Nilufar Olimjanovna; Nematullayev Quvonchbek Jamshidovich; Sharofiddinova Umida Sharofiddin qizi; Ravshanov Sodiqjon Odil ogli (Web of Journals Publishing, 2024)
This article presents the results of monitoring various deflation processes on irrigated lands in the districts of the Jizzakh region, as well as the results of determining the level of risk of deflation in soils.
Keywords: Deflation, soil fertility, intercropping, current issue, morphological features.